Human-divine interactions in the Hebrew scriptures: covenants and cross-purposes - Lerner, Berel Dov (Routledge interdisciplinary perspectives on biblical criticism, 2024)
"This book addresses central theological issues and biblical narratives in terms of a bold thesis regarding relations between God and humans: that the actions of God and the actions of humans are informed by independently valid moral viewpoints which do not entirely overlap. The author suggests that God's plans and actions reflect the interests and obligations appropriate to His goal of creating a worthy world, but not necessarily our world. In contrast, humans must attend to special obligations grounded in their dependence on their existing created world and in their particular places in the human family. However, in acts of grace, God voluntarily takes on special obligations towards the created world by entering into covenants with its inhabitants. When the covenant involves reciprocal obligations, as in the case of God's covenant with Israel, it also recruits human beings to play conscious roles in God's larger plans. These covenants frame the moral parameters of divine/human interaction and cooperation in which each party strains to negotiate conflicts between its original duties and the new obligations generated by covenants. The interpretive discussions in this book involve close readings of the Hebrew text and are also informed by rabbinic tradition and Western philosophy. They address major issues that are of relevance to scholars of the bible, theology and philosophy of religion, including the relationship between divine commands and morality, God's responsibility for human suffering, God's role in history, and the intersection between politics and religion"--